Diagnostic Value of Bronchoalveolar Lavage Fluid Metagenomic Next-Generation Sequencing in Pneumocystis jirovecii Pneumonia in Non-HIV Immunosuppressed Patients - Sun, He; Wang, Feilong; Zhang, Ming; Xu, Xiaoyong; Li, Miaomiao; Gao, Wei; Wu, Xiaodong; Han, Huize; Wang, Qin; Yao, Gehong; Lou, Zheng; Xia, Han; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction This study aims to assess the value of metagenomic next-generation sequencing (mNGS) of bronchoalveolar lavage fluid (BALF) in the diagnosis of Pneumocystis jirovecii pneumonia (PJP) and its mixed infection in non-human immunodeficiency virus (HIV) immunosuppressed patients. Methods A total of 198 non-HIV immunosuppressed patients with severe pneumonia were enrolled, including 77 PJP patients and 121 patients infected by other pathogens. BALF-mNGS and traditional detection methods were used. Results The positive detection rate of various pathogens of BALF-mNGS was higher than that of the conventional methods, especially for mixed pathogens. The sensitivity and specificity of BALF-mNGS for the diagnosis of PJP were 97.40% and 85.12%, respectively. Compared with traditional methods, the sensitivity of BALF-mNGS was significantly higher than that of blood fungal G (BG)/lactate dehydrogenase (LDH) and BALF-microscopy (p<0.05), and its specificity was significantly higher than that of BG/LDH (p<0.05). In addition, the average detection time of BALF-mNGS (32.76 ± 10.32 h) was also significantly shorter than conventional methods (p<0.01), especially for mixed infections that were common in non-HIV immunosuppressed patients. In patients only detected as positive by BALF-mNGS, the underlying diseases mainly manifested as hematological malignancies with agranulocytosis and within 8 months after hematopoietic stem cell or solid organ transplantation. Conclusions BALF-mNGS technology is faster, more sensitive, and more comprehensive in detecting P. jirovecii and its mixed infection in immunosuppressed patients.